Perancangan UI/UX Aplikasi Debt Note dengan Metode Design Thinking - Muhammad Khairul Faizi Islamy; Faris Afada; Ranu Arva Adristiawan; Indrawan Ady Saputro (Indonesian Journal Publisher, 2025)
The rapid development of technology has encouraged digitalization in various aspects of life, including in the case of financial records. One of the problems that is often faced is debt recording which is still traditionally carried out using paper media, which is vulnerable to damage, loss, and manipulation of data. To answer this challenge, the Debt Note application is designed to make it easier to record debts digitally. The design of this application uses a method called Design Thinking which includes five stages, namely Empathize, Define, Ideate, Prototype, and Testing. This research aims to develop an easy-to-use application, especially for store owners, in order to manage debt data better and efficiently. The results of the feasibility test using the System Usability Scale (SUS) method show an average score of 90, which is included in the Excellent category, reflecting a high positive response from users to the application. The Debt Note application provides various features such as debt recording, repayment, and mobile-based data management with an intuitive and efficient interface design. The designer hopes that this application can be implemented in various areas of the store and can reduce the level of loss and damage in a debt recording data that causes quarrels between store owners and buyers.